2022
DOI: 10.18632/aging.203899
|View full text |Cite
|
Sign up to set email alerts
|

PERK activation by SB202190 ameliorates amyloidogenesis via the TFEB-induced autophagy-lysosomal pathway

Abstract: The protein kinase R (PKR)-like endoplasmic reticulum (ER) kinase (PERK), a key ER stress sensor of the unfolded protein response (UPR), can confer beneficial effects by facilitating the removal of cytosolic aggregates through the autophagy-lysosome pathway (ALP). In neurodegenerative diseases, the ALP ameliorates the accumulation of intracellular protein aggregates in the brain. Transcription factor-EB (TFEB), a master regulator of the ALP, positively regulates key genes involved in the cellular degradative p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Interestingly, SB202190 was shown to induce TFE3/TFEB activation and regulate autophagy and lysosome biogenesis independent of p38 inhibition (Yang et al, 2020). Recent studies indicate that the effect of SB202190 on TFEB nuclear localisation is mediated by p38-independent EIF2AK3/PERK activation (Do et al, 2022). Unlike the micron-scale vacuole formation, these effects on TFEB and PERK activation were not reported to be cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SB202190 was shown to induce TFE3/TFEB activation and regulate autophagy and lysosome biogenesis independent of p38 inhibition (Yang et al, 2020). Recent studies indicate that the effect of SB202190 on TFEB nuclear localisation is mediated by p38-independent EIF2AK3/PERK activation (Do et al, 2022). Unlike the micron-scale vacuole formation, these effects on TFEB and PERK activation were not reported to be cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…[29,39] Consistently, in neuroblastoma cells, EIF2AK3 activated Ca 2+ and calcineurin which promoted TFEB nuclear translocation. [42] Carbon monoxide increased mitophagy through TFEB activation by EIF2AK3-increased intracellular Ca 2+ and activity of calcineurin. [43] Thus, our results suggested that SiNP-induced TFEB activation might depend on EIF2AK3-Ca 2+ -calcineurin axis.…”
Section: Discussionmentioning
confidence: 99%
“…As lysosomal acidity increases in DCs, the efficiency of cross-presentation wanes due to the premature state of phagosomes. In particular, p38 likely acts as a negative regulator of TFEB-mediated lysosomal biogenesis, especially in microglia ( 65 67 ). Hence, careful modulation of lysosomal activity mediated by p38-TFEB signaling axis is also likely critical in determining the fate of an internalized antigen and in regulating the balance between the two exogenous antigen-presenting pathways in DCs.…”
Section: Molecular Mechanisms Of Dendritic Cell Cross-presentationmentioning
confidence: 99%